FEAR OF NEGATIVE SELF EVALUATION AND EMOTIONAL SELF-REGULATION AMONG COLLEGE STUDENTS: MEDIATE BETWEEN NEGATIVE PHYSICAL SELF-IMAGE AND SOCIAL ANXIETY - Binish Nighat; Yousaf Khan; Bakhtawar; Rashid Hameed (International Journal of Contemporary Issues in Social Sciences, 2024)
The objective of this study is to investigate the correlation between an unfavorable perception of one's physical appearance and the presence of social anxiety among college students. Additionally, it analyses the moderating influences of fear of unfavorable evaluation and regulatory emotional self-efficacy. This study aims to investigate the fundamental mechanisms and influential elements that contribute to social anxiety. A total of 524 undergraduate students completed four distinct assessments: the Negative Physical Self-Scale, the Interaction Anxiety Scale, the Regulatory Emotional Self-Efficacy Scale, and the Brief Fear of Negative Evaluation Scale. We employed SPSS 26.0 software to conduct data analysis, specifically utilizing the Bootstrap test to determine the statistical significance of the mediating effects. Among college students, there existed a robust association between social anxiety and a detrimental opinion of one's physical appearance. The connection was mediated by independent factors, namely the regulation of emotional self-efficacy and fear of unfavorable assessment. A reciprocal chain mediation effect was observed, whereby the management of emotional self-efficacy and fear of unfavorable assessment jointly influenced the relationship between social anxiety and a negative perception of one's physical appearance. This study elucidates the correlations between social anxiety and a detrimental impression of one's physical appearance. The results indicate that both the independent and bidirectional effects of modulating emotional self-efficacy and fear of unfavorable appraisal play a role in mediating the connection between social anxiety and negative physical self-image. Lawmakers and educators should seriously evaluate these findings if they are committed to developing solutions that assist college students in overcoming social anxiety.